Literature on organizational innovation: Past and future - Marlon Fernandes Rodrigues Alves; Simone Vasconcelos Ribeiro Galina; Silvio Dobelin (Innovation & Management Review, 2018)
Purpose: The purpose of this paper is to examine what are both the main theoretical basis and the recent perspectives within the organizational innovation literature. Design/methodology/approach: The authors have conducted a bibliometric analysis reviewing the research on organizational innovation from 460 articles published in the period from 2007 to 2016 and indexed in the Web of Science through co-citation and bibliographical coupling analyses. Findings: The clusters analysis results show that the main theoretical foundations are learning and evolution; implementation of innovation; and leadership, creativity and learning. Regarding recent perspectives, the clusters indicate studies on core concepts, knowledge and capability, learning for resource development and human resources for innovation. Originality/value: This study organizes the knowledge basis for future research on organizational innovation, and, unlike most literature reviews, this study provides the current trends on the topic and presents a comprehensive research agenda.
Keywords: 650; Literature review; Learning; Capabilities; Leadership; Organizational innovation